PENGARUH KOMPETENSI, KOMITMEN INDIVIDUAL DAN MOTIVASI TERHADAP KINERJA TENAGA PENDIDIK DI SPN BATUA SULAWESI SELATAN - Mahmud Mahmud; Hasmin Hasmin; Gunawan Gunawan (AkMen JURNAL ILMIAH, 2016)
The purpose of this study was to (1) analyze the simultaneous effect of competence, individual commitment and motivation on the performance of teachers in the State Police School Batua South Sulawesi Regional Police, and (2) determine which variables are the dominant influence on the educators performance in the State Police School Batua Police South Sulawesi. The data used are primary data and secondary data. The population in this study were students, structural, and educators with a total of as many as 67 people in the State Police School Batua South Sulawesi Police. The sampling method in this study using purposive sampling method that is selected based on certain considerations. Data collected through observation, questionnaire, and documentation. Methods of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS version 22. The results showed that either simultaneously or in partial, competence, individual commitment, and motivation positive and significant impact on the performance of teachers in the State Police School Batua South Sulawesi Police. Of the three independent variables were significant, it appeared variable competence of the dominant influence in improving the educators performance in the State Police School Batua South Sulawesi Police.